The Relationship Between Maternal Knowledge and Vitamin A Capsule Consumption Behavior - iwan saka nugraha; I Kadek Sudiarta; Made Prita Artika (Institut Kesehatan YARSI Mataram, 2026)
Vitamin A is an essential micronutrient important in maintaining healthy vision and immunity, especially in toddlers. This study aims to determine the characteristics of respondents (age, education level, income, occupation, knowledge, access to health services, and family support) regarding the taking of vitamin A capsules in toddlers and to determine the relationship between maternal knowledge and taking of vitamin A capsules in toddlers. The ties in the East Bali work area. This study used a quantitative approach with a cross-sectional design and a purposive sampling technique. The number of samples was 186 respondents. Data were collected through questionnaires that had been tested for validity and reliability, and analyzed using SPSS software through univariate and bivariate tests (Chi-square). The results showed that there was a significant relationship between maternal knowledge and the behavior of taking vitamin A capsules in toddlers (p <0.05). Taking vitamin A capsules in toddlers is influenced by socio-economic and cognitive factors of the mother. There is a need for holistic interventions that include increasing health education, easy access to services, and active family involvement in child health programs to increase the coverage of vitamin A provision in the community.